Clinico Microbiological Study of Infection In Burn Patients at BPKIHS Teaching Hospital - Thapaliya, Narad Prasad (Journal of National Heart and Lung Society Nepal, 2024)
Background: Each year around 2,00,000 peoples globally are injured by burn and 1,00,000 of these seek medical attention out of which 10,000 lose their lives. prevention is better in burns. The exact data about burns patient in Nepal is not known. Methods: Prospective observational study carried out at surgical ward of BPKIHS Teaching Hospital between 15 May 2001 to 14 May, 2002 i.e. one year altogether. Results: There were total 95 cases of burn patients admitted and managed by BPKIHS Teaching Hospital during that periods. Males were 40% (38) and Females were 60% (57). Accidental burns injury was 90.55% (86) and flame burns were 83% (79). Mixed infection in 36%, Acinobacter in 32% and pseudomonas in 14.4% found in wound swab cultures. Ofloxacin was found sensitive in 91.6%. 27% (26) patients expired in our study. Conclusion: Mortality is high in our study because of Major burn patients came late in our Teaching Hospital for treatment.